RELATIONSHIP OF INDIVIDUAL CHARACTERISTICS, PHYSICAL HOME ENVIRONMENT AND BEHAVIOR WITH THE INCIDENCE OF PULMONARY TB IN CIJORO PASIR VILLAGE, MUARA VILLAGE EAST CIUJUNG AND WEST RANGKASBITUNG VILLAGE, RANGKASBITUNG SUBDISTRICT, LEBAK REGENCY 2019 - Rojali, Rojali; Sari, Dwita Indah (ADI Publisher, 2020)
This study entitled